Physical and Sensory Characteristics of Bread from Composite Wheat and Cassava Flours with Optimum Fermentation and Proportional Water Volume - Rauf, Rusdin; Sarbini, Dwi; Nurdiana, N (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2017)
The purpose of the research was to evaluate the physical characteristics and sensory of bread from the composite flours of wheat and cassava with optimum fermentation and the proportional water volume. The study was conducted by optimizing the fermentation of the dough and using the proportional water volume. The research was conducted with 4 treatments of composite wheat flour and cassava flour, which were 100: 0, 90:10, 80:20, and 70:30. The bread was then tested for the expansion, hardness, elasticity and sensory acceptance. The results indicated that the higher portion of cassava flour, the lower the expansion of bread. The highest expansion of bread was given by the 100: 0, which was 64.9 mm for 55 min fermentation. The highest hardness of bread was displayed by the 70:30, which was 3482.7 g for 75 min fermentation and 3372 g for 85 min fermentation, whereas, the lowest hardness of bread was shown by the 100:0, was 1355.3 g for 55 min fermentation. Variations of composite flour ratios of wheat and cassava flours affected the color, aroma, taste, texture and overall acceptance of bread. The composite flour 100:0 gave the highest overall sensory acceptance, followed by the 80:20.